The French Experience from Republic to Monarchy, 1792-1824
XII, 230 p.
Keywords: Fourteen wide-ranging chapters by distinguished international scholars treat key aspects of the rapidly changing political and cultural scene in France from the First Republic, through the Consulate and Empire to the death of Louis XVIII in 1824. Falling into two interlinked parts, this collection of original essays explores new developments as well as continuities characterising the transition between the eighteenth century and the nineteenth. It includes chapters on feminism, politics and theatre, elections and plebiscites, revolution and counter-revolution, patronage, universities and education, medicine, music and science.